Early and middle Miocene ice sheet dynamics in the Ross Sea: results from integrated core-log-seismic interpretation - Pérez,LF; De,Santis L; McKay,RM; Larter,RD; Ash,J; Bart,PJ; Böhm,G; Brancatelli,G; Brown,I; Colleoni,F; Dodd,JP; Geletti,R; et al. (GSA Bulletin, 2022)
Oscillations in ice sheet extent during early and middle Miocene are intermittently preserved in the sedimentary record from the Antarctic continental shelf, with widespread erosion occurring during major ice sheet advances, and open marine deposition during times of ice sheet retreat. Data from seismic reflection surveys and drill sites from Deep Sea Drilling Project (DSDP) Leg 28 and International Ocean Discovery Program (IODP) Expedition 374 located across the present-day middle continental shelf of the central Ross Sea, indicate the presence of expanded early to middle Miocene sedimentary sections. These include the Miocene Climate Optimum (MCO ∼17-14. 6 Ma), and the Middle Miocene Climate Transition (MMCT ∼14.6-13.9 Ma). Here, we correlate drill core records, wireline logs and reflection seismic data to elucidate the depositional architecture of the continental shelf and reconstruct the evolution and variability of dynamic ice sheets in the Ross Sea during the Miocene. Drill-site data are used to constrain seismic isopach maps that document the evolution of different ice sheets and ice caps which influenced sedimentary processes in the Ross Sea through the early to middle Miocene. In the early Miocene, periods of localized advance of the ice margin are revealed by the formation of thick sediment wedges prograding into the basins. At this time, morainal bank complexes are distinguished along the basin margins suggesting sediment supply derived from marine-terminating glaciers. During the MCO, biosiliceous-bearing sediments are regionally mapped within the depocenters of the major sedimentary basin across the Ross Sea, indicative of widespread open marine deposition with reduced glacimarine influence. At the MMCT, a distinct erosive surface is interpreted as representing large-scale marine-based ice sheet advance over most of the Ross Sea paleo-continental shelf. The regional mapping of the seismic